ANALYSIS OF ERROS IN SOLVING COUNT OPERATION PROBLEM IN ALGEBRAIC FORM BASED ON INITIAL ABILITY OF GRADE VII STUDENTS AT SMP NEGERI 01 KILO - Rasul, A. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
The results of the study reveal that (1) the type of errors happened to subjects wits high, fair, and low abilities by not stating or writing the requirement to solve the questions. Other type of errors also happened to subjects with low ability by not identifyng appropriately the elements in Algebra and not explaining appropriately systematic steps in solution. The place of errors happened to subjects with high, fair, and low abilies by not manipulating appropriatelyalgebraic form and not counting appropriately in: other place of errors also happened to subjects with low abilities by conductting irregularities of steps and not writing the variables in solving the questions; (2) the causes of errors happened to subjects with high, fair, and low categories by not undertanding the requirement to solve the questions, having diffculty of understanding the concept of variables, coefficient, and contanta, students tended to memorize than understand, lack of understanding of multiplication operation between two algebraic forms, and often forget the previus lessons. Other errors also happened to subjects wits fair and low abilities among others were not understanding division operation in Algebra particularly division with brackets, confused with the questions, using multiplication operation between two Algebraic forms, confused in solving Algebraic forms which had long and reversed solutions, and counfused when getting the counting which involved positive (+) sign and negative (-) sign